Endowing imidazole derivatives with thermally activated delayed fluorescence and aggregation‐induced emission properties for highly efficient non‐doped organic light‐emitting diodes. Issue 2 (30th September 2021) - Yang, Ge; Ran, You; Wu, Yimin; Chen, Minqi; Bin, Zhengyang; You, Jingsong
Abstract: The development and enrichment of high‐performance organic fluorophores that simultaneously possess thermally activated delayed fluorescence (TADF) and aggregation‐induced emission (AIE) properties is going pursued but remains a great challenge due to severe exciton quenching. Herein, a systematical investigation on imidazole moiety has successfully given rise to a series of highly efficient imidazole‐based TADF‐AIE luminogens for the first time. The attachment of two cyano functionalities on imidazole moiety can significantly increase the electron‐withdrawing ability, so as to realize TADF emissions with small singlet‐triplet energy gaps (Δ E ST ) values. Meanwhile, the installation of a steric hindrance group at N1 position of imidazole moiety can twist the geometry between imidazole and phenyl bridge, thus transforming imidazole derivative from an aggregation‐caused quenching emitter into an AIE luminogen. Consequently, the non‐doped organic light‐emitting diodes (OLEDs) utilizing these TADF‐AIE luminogens as emitters exhibit outstanding sky‐blue and green emissions, with external quantum efficiency (EQE) as high as 20.0% and low efficiency roll‐off (EQE at 1000 cd m −2, 16.1%). These values represent the state‐of‐the‐art performance for all imidazole‐based OLED devices, which illustrates the significant potential of imidazole derivatives in assembling high‐performance OLEDs. Abstract : The first example of imidazole‐based TADF‐AIE luminogen has been developed, which exhibits state‐of‐the‐art OLED performance with EQEmax as high as 20.0% and impressively low efficiency roll‐off.